Prognostic Impact of Late Gadolinium Enhancement by Cardiovascular Magnetic Resonance in Myocarditis: A Systematic Review and Meta-Analysis. (January 2021) - Georgiopoulos, Georgios; Figliozzi, Stefano; Sanguineti, Francesca; Aquaro, Giovanni Donato; di Bella, Gianluca; Stamatelopoulos, Kimon; Chiribiri, Amedeo; Garot, Jerome; Masci, Pier Giorgio; Ismail, Tevfik F.
Abstract : Background: Patients with acute myocarditis (AM) are at increased risk of adverse cardiac events after the index episode. Late gadolinium enhancement (LGE) detected by cardiovascular magnetic resonance in patients with AM plays an important diagnostic role, but its prognostic significance remains unresolved. This systematic review and meta-analysis sought to assess the prognostic implications of cardiovascular magnetic resonance-derived LGE in patients with AM. Methods: Data search was conducted from inception through February 28, 2020, using the following Medical Subject Heading terms: Myocarditis, CMR, Magnetic Resonance Imaging, Magnetic Resonance . From 2422 articles retrieved, we selected 11 studies reporting baseline cardiovascular magnetic resonance assessment and long-term clinical follow-up in patients with AM. Hazard ratios and CIs for a combined clinical end point were recorded for LGE presence, extent (>2 segments or >10% of left ventricular [LV] mass or >17g) and location (anteroseptal versus non-anteroseptal). A combined end point comprised all-cause mortality, cardiac mortality, and major adverse cardiovascular events. Hartung and Knapp correction improved robustness of the results. Prespecified sensitivity analyses explored potential sources of heterogeneity. The meta-analysis was conducted according to the Meta-analysis of Observational Studies in Epidemiology guidelines. Results: LGE presence (pooled hazard ratios, 3.28 [95% CIs, 1.69–6.39], P <0.001 [95% CIs, 1.33–8.11] after Hartung and Knapp correction) and anteroseptal LGE (pooled-hazard ratios, 2.58 [95% CIs, 1.87–3.55], P <0.001 [95% CIs, 1.64–4.06] after Hartung and Knapp correction) were associated with an increased risk of the combined end point. Extensive LGE was associated with worse outcomes (pooled-hazard ratios, 1.96 [95% CIs, 1.08–3.56], P =0.027), but this association was not confirmed after Hartung and Knapp correction (95% CIs, 0.843–4.57). Conclusions: LGE presence and anteroseptal location at baseline cardiovascular magnetic resonance are important independent prognostic markers that herald an increased risk of adverse cardiac outcomes in patients with AM. Registration: https://www.crd.york.ac.uk/PROSPERO/ Unique identifier: CRD42019146619. Abstract : Supplemental Digital Content is available in the text.